ANALISIS ANTRIAN DAN TUNDAAN AKIBAT PENUTUPAN PINTU PERLINTASAN KERETA API TERHADAP KINERJA LALU LINTAS DI SIMPANG STASIUN BEKASI - Marulin Febrita Lukita; Susanty Handayani; Zaenal Abidin (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The crossing of a plot between the Railway and the highway on the road Perjuangan often causes problems, especially if the crossing door is closed when the Railway passes. The problem is that queues and vehicle times return to normal shortly after the crossing door is opened on Ir. H. Juanda, Bekasi. This study aims to determine the potential for delays and queues related to the operating time of the crossing door of a plot at the Bekasi Station Crossing. This research uses a quantitative approach using linear regression and vissim software to perform analysis. The results of the analysis and discussion showed a significant influence on the variables of the number of trains passing at the crossing of a plot, delay, and vehicle queue lengths. In addition, the Road Geometry variable affects the length of queues and vehicles’ delays road. Ir. H. Juanda, Bekasi. The results of this study are expected to be used as a consideration in handling traffic management and can minimize the occurrence of traffic congestion